Kinerja Efisiensi Industri Perbankan Indonesia: Bank Pembangunan Daerah - Lis Sintha (JURNAL MITRA MANAJEMEN, 2014)
AbstractTo achieve maximum benefit level, a company must be able to produce the optimaloutput level with a certain number of inputs (technical efficiency) and produces output with theright combination at a certain price level (allocative efficiency). The concept of efficiencymeasurement can be viewed either with a focus on the input side (input-oriented) or focus onthe output side (output-oriented). The second approach is analogous to the concept of theprimal and dual operations research techniques, which are like two sides of a coin, so that thetwo approaches will consistently produce the same conclusions about the relative efficiency ofa company to the relationship.For BPD who are not able to achieve 100% efficiency rating, to achieve the maximumvalue of the bank should increase total loan and total revenue portfolio. For the banks withBPD, especially medium and small can take several policies to improve the efficiency of theoptimal performance, through economics of scale in operations and focus on lending to micro,small and medium enterprises (SMEs). In addition, monetary authorities and governmentshould consider to from a Local Credit Guarantee Agency (LCGA). Credit guarantee is thecomplement of a credit system and can serve as a substitution for collateral, despite subograsibilling remains the duty of the creditor.Keywords: EfficiencyBank, Regional Development Banks (BPD)